Accelerometer load profiles for basketball-specific drills in elite players - Schelling, X.; Torres, L. (Journal of Sports Science & Medicine, 2016)
The purpose of this study was to quantify the workload during basketball-specific drills measured through microtechnology. Twelve professional male basketball players from the Spanish 1st Division were monitored over a 4-week period. Data were collected from 16 sessions, for a total of 95 ± 33 drills per player. Workload data (Acceleration load; AL) were obtained from a tri-axial accelerometer at 100Hz sampling frequency, and were expressed over time (AL.min-1). Comparisons among training drills (i.e., 2v2, 3v3, 4v4, and 5v5) were assessed via standardized mean differences. Full-court 3v3 and 5v5 showed the highest physical demand (AL.min-1: 18.7 ± 4.1 and 17.9 ± 4.6, respectively) compared with other traditional balanced basketball drills such as 2v2 and 4v4 (14.6 ± 2.8 and 13.8±2.5, respectively). The AL.min-1 on half-court showed trivial-to-moderate differences with a likely increase of ~10-20% in 2v2 drill compared with any other formats. This study provides insight into the specific requirements of a range of exercises typically performed in basketball sessions. The use of accelerometer data is presented as a useful tool in assessing the workload.